2008
DOI: 10.1007/s10745-008-9172-7
|View full text |Cite
|
Sign up to set email alerts
|

The Local Perception of Tropical Deforestation and its Relation to Conservation Policies in Los Tuxtlas Biosphere Reserve, Mexico

Abstract: We examine the ways both deforestation and conservation are viewed by people of two villages with different ethnic composition located within the biosphere reserve of Los Tuxtlas, Mexico. The rain forest is considered to be important, since it provides many resources and environmental benefits. Residents do notice forest degradation, although deforestation is not one of their major concerns. In the mestizo village, 65% of interviewees indicated they felt responsible for deforestation, while only 30% of indigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
2
33
0
2
Order By: Relevance
“…Part of the problem is that these projects are largely dependent on external support and not on local incentives that will build human capacity [45,49]. In this sense, OMYK is consistent with conventional conservation approaches where the participation of locals in the implementation and management of conservation programs is restricted [14,58], even though most group categories suggested that the PA should represent the interests of all parties involved, in particular local communities.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Part of the problem is that these projects are largely dependent on external support and not on local incentives that will build human capacity [45,49]. In this sense, OMYK is consistent with conventional conservation approaches where the participation of locals in the implementation and management of conservation programs is restricted [14,58], even though most group categories suggested that the PA should represent the interests of all parties involved, in particular local communities.…”
Section: Discussionmentioning
confidence: 96%
“…Views on the role of protected areas vary according to group interests [14,16,17,45]. Although OMYK's stakeholders expressed different interests in the PA, all groups shared a collective vision of the goals that should be prioritized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a mangrove deforestation study in Cameroon, for example, lack of flooding and deforestation risk perception meant that mangrove protection would be limited (Munji et al 2014). Diverse perceptions of causes of deforestation influenced degrees of interest in conservation in Los Tuxtlas, Mexico (Durand and Lazos 2008).…”
Section: Introductionmentioning
confidence: 99%